Religious meaning system and life satisfaction: the mediating role of meaning in life among Polish people with multiple sclerosis - Wilski, Maciej; Wnuk, Marcin; Brola, Waldemar; Szcześniak, Małgorzata; Żak, Marek; Sobolewski, Piotr; Kapica-Topczewska, Katarzyna; Tarasiuk, Joanna; Czarnowska, Agata; Kułakowska, Alina; Zakrzewska-Pniewska, Beata; Bartosik-Psujek, Halina; et al. (Frontiers in Psychiatry, 2024)
The complexity of the associations between religiosity and indicators of well-being suggests the presence of a mediating mechanism. Previous studies indicate that religion may influence subjective well-being because it helps to find meaning and purpose. Therefore, the aim of our study was to examine the mediating role of the presence and search dimensions of meaning in life in the relationship between religious meaning system and life satisfaction in patients with multiple sclerosis (MS). This cross-sectional study included 600 MS patients recruited from Poland who completed the Satisfaction with Life Scale (SWLS), the Religious Meaning System Questionnaire (RMS) and the Meaning in Life Questionnaire (MLQ). Model 6 of Hayes PROCESS was used to test the hypotheses. The results of our research indicate that there was a significant indirect effect of religious meaning system on life satisfaction through the presence of meaning in life. The specific indirect effect of religious meaning system on life satisfaction through searching for meaning in life was not significant. The results of our study are relevant because they show that religion as a meaning system is positively related to the presence of meaning in life, which in turn positively predicts life satisfaction. This is particularly important in the case of incurable illness, where finding meaning in life is one of the natural stages of adaptation. By incorporating these findings into mental health practice, professionals can enhance the holistic well-being of people coping with MS and contribute to a more comprehensive and effective approach to mental health care.